ANTHROPOLOGIST AMONG THE HISTORIANS AND OTHER ESSAYS - BERNAD S COHN (NEW DELHI OXFORD UNIVERSITY PRESS, 1988)
Concerned with the Indian subcontinent in the colonial period, these essays concentrate on methodology within the disciplines of history and anthropology, particularly as they relate to India, as well as anthropological history.
Keywords: SOCIAL CONDITIONS - INDIA; ANTHROPOLOGY - METHODOLOGY